NGHIÊN CỨU QUÁ TRÌNH SINH ĐỊA HÓA TRONG HỆ THỐNG “THẢM THỰC VẬT - VẬT RƠI RỤNG - ĐẤT” TẠI RỪNG NHIỆT ĐỚI THUỘC VƯỜN QUỐC GIA BIDOUP-NÚI BÀ - R. V., Gorbunov; Ya. O., Lebedev; Phạm, Cầm Nhung; A. V., Drygval; T. Yu., Gorbunova; A. N., Kuznetsov; S. P., Kuznetsova; Nguyễn, Đăng Hội (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
STUDY OF BIOGEOCHEMICAL PRIOCESSES IN THE VEGETATION - LITTER - SOIL SYSTEM IN MOUNTAIN TROPICAL FORESTS OF BIDUP-NUIBA NATIONAL PARK The study of geochemical processes is an urgent task for understanding the functioning of the little-studied system "vegetation-litter-soil" and the biosphere as a whole. In mountainous areas, the processes of soil formation acquire unique features and are complicated by the processes of redistribution of matter. This work introduces the results of studies of geochemical processes in 2018-2022 on the territory of the Bidoup-Nui Ba National Park (Central Vietnam) during the wet and dry seasons. The influence of the relief on the formation of plant mortmass and the change in the ash content of fallen branches and leaves is considered. The results of studies of vertical and horizontal migration of chemical elements in soils of mid-mountain primary tropical monsoon forests are presented. Regularities of geochemical migration of chemical elements within all types of elementary geochemical landscapes, from autonomous to accumulative, are revealed. The existence in soils of several geochemical barriers characteristic of zheltozems has been revealed. The study made it possible to clarify the elements that are most actively involved in biogeochemical migration and accumulation in different seasons of the year, to assess the biogeochemical mobility of elements and the intensity of the processes of their biological accumulation by bamboo organs growing in different landscape conditions in the wet and dry seasons of the year. The research results make it possible to identify the features and patterns of changes in the content of trace elements in the "vegetation-litter-soil-soil" system, their biological accumulation and biogeochemical mobility during the wet and dry seasons in the Bidoup-Nui Ba National Park. The paper also presents the results of a study of soil samples for the presence of heavy metals, taken in the Bidoup-Nui Ba National Park. In the course of this study, native Cd contamination was detected in concentrations typical for objects subjected to technogenic pollution.